Plugging the explicit σ-holes in molecular docking - Kolář, Michal; Hobza, Pavel; Bronowska, Agnieszka K (Chemical communications (Cambridge, England), 2013)
A novel approach in molecular docking was successfully used to reproduce protein-ligand experimental geometries. When dealing with halogenated compounds the correct description of halogen bonds between the ligand and the protein is shown to be essential. Applying a simple molecular mechanistic model for halogen bonds improved the protein-ligand geometries as well as halogen bond features, which makes it a promising tool for future computer-aided drug development.
Keywords: Drug Design; Ligands; halogenované uhlovodíky; Models, Molecular; proteiny; molekulární modely; kvantová teorie; Computer-Aided Design; racionální návrh léčiv; Hydrocarbons, Halogenated; ligandy; Quantum Theory; Proteins; design s pomocí počítače